Pelaksanaan Pemberian Hibah Berdasarkan Hukum Adat Di Nagari Salayo Kabupaten Solok - Muhammad Tegar Adhiyatma; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Customary law is the whole custom (which is not written) and lives in society in the form of morals, habits, and customs which have legal consequences which in this case is regulated in Article 18B Paragraph (2) of the 1945 Constitution. One of the customary laws in Indonesia is The Minangkabau Indigenous People have their own rules in regulating their communities, especially in the distribution of pusako assets. Minangkabau pusako assets are divided into two, namely high pusako assets and low pusako assets, in this case they are related to grants. The problem with the implementation of grants based on customary law that the author wants to examine is one of the problems of grants that occurred in Nagari Salayo, the implementation of this gift was a high pusako grant in the form of land with wooden buildings on it, because it happened not because the descendants of the people became extinct but at that time the recipient The heir was still small and there was no word of consensus, therefore Moechtar donated high pusako property to his son, Misnawati, the Parak Panjang tribe. The formulation of the problems in this thesis are: First, how is the grant implementation in Nagari Salayo, Solok Regency? Second, how is the legal protection of the high pusako grant in Nagari Salayo, Solok District?The type of research used is sociological research, because in this study directly conducted research at the location in order to provide a complete picture and type of the problem under study. This research was conducted by Nagari Salayo, Kubung District, Solok Regency, West Sumatra Province, while the population and sample were all parties concerned with the problems studied with this study. The data sources used were prime data, secondary data and special data. Data collection techniques in this study were interviews and literature study.From the research results, there are two main points that can be rejected. First, the implementation of grants in Nagari Salayo legally takes place according to local customary law with the main requirement of mutual agreement or known as mufakat, this agreement includes the head of the inheritance mamak, ninik mamak, kamanakan, and also the women of the clan. Second, the legal protection of high pusako grants in Nagari Salayo is regulated in which customary law is derived from the principle of customary law itself.Keywords: heirlooms, grants, indigenous Nagari Salayo